2009
DOI: 10.1007/s11096-009-9347-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy services to UK Emergency Departments: a descriptive study

Abstract: Pharmacy services have developed to support service provision in EDs with similar roles to in-patient pharmacists. Pharmacy services in some EDs are now extensive with funded, full-time pharmacy posts but pharmacy service review is required to optimise ED patient care where there is limited or no current pharmacy input. New pharmacy services must fit with local ED service models and skill mix. Evaluation of these new services is vital to maximise benefit to patients and the NHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
0
16
1
1
Order By: Relevance
“…A prospective evaluation of adverse drug interactions in the emergency department reported potential drug interactions in 18% of all patients not restricted to old age; 15% of potential drug interactions were found to be clinically relevant which corresponds with 5% of all patients (41). A prospective (43) and a retrospective (2) study in older patients presenting to the emergency department found potential adverse drug interactions in 27% and 31% respectively; however, in contrast with our study, the authors did not look at the clinical significance in the individual patients and, due to the retrospective a closer collaboration between general practitioners and pharmacists can improve patient care and may reduce medication-related morbidity and mortality (58,59). On the other hand, it is difficult to estimate the efficacy of such interventions since simply having defined a posteriori an ADR as avoidable, is not enough to imply that the event could have been avoided.…”
Section: Discussioncontrasting
confidence: 74%
“…A prospective evaluation of adverse drug interactions in the emergency department reported potential drug interactions in 18% of all patients not restricted to old age; 15% of potential drug interactions were found to be clinically relevant which corresponds with 5% of all patients (41). A prospective (43) and a retrospective (2) study in older patients presenting to the emergency department found potential adverse drug interactions in 27% and 31% respectively; however, in contrast with our study, the authors did not look at the clinical significance in the individual patients and, due to the retrospective a closer collaboration between general practitioners and pharmacists can improve patient care and may reduce medication-related morbidity and mortality (58,59). On the other hand, it is difficult to estimate the efficacy of such interventions since simply having defined a posteriori an ADR as avoidable, is not enough to imply that the event could have been avoided.…”
Section: Discussioncontrasting
confidence: 74%
“…This provides some evidence that the potential functions of the system in supporting the management of medication-related complications and order writing skills on hand and decreasing drug interactions and managing medication inventory on the other, have been ignored. [25]…”
Section: Resultsmentioning
confidence: 99%
“…This study revealed that just 40% of the medication information requirements are recorded in the Pharmacy Information Systems in form of description. This provides some evidence that the potential functions of system in supporting the management of medication-related complications and order writing skills on the one hand and decreasing drug interactions and managing medication inventory on the other, have been ignored (24). Likewise, Azizi (2005) in his study found that the mean scores of meeting the standards determined by the American Physicians College in order writing & medication information maintenance in the PISs applied in Iran, Tehran and Shahid Beheshti Universities of Medical Sciences were 28.5%, 26.6% and 31.1%, respectively (25).…”
Section: Discussionmentioning
confidence: 99%